Silicon quantum dot cross-linking agent for gel type plugging agent and preparation method of silicon quantum dot cross-linking agent

By modifying the silicon quantum dots, epoxy silicon quantum dot crosslinking agent with multiple functional groups is prepared, which solves the shortcomings of the existing frozen glue-type plugging agent crosslinking agent in crosslinking speed and stability, and achieves high strength and resistance Improved aging performance, suitable for high-temperature and high-salt environments in oil fields.

CN119286487AActive Publication Date: 2025-01-10CHINA UNIV OF PETROLEUM (EAST CHINA)
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202411397666.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-09
Publication Date
2025-01-10
Estimated Expiration
2044-10-09

AI Technical Summary

Technical Problem

The crosslinking agents of existing frozen glue-type plugging agents have shortcomings in terms of fast crosslinking speed, poor stability, easy failure, high cost, poor salt resistance, etc., which are difficult to meet the needs of oil fields in high temperature and high salt environments.

Method used

By modifying the silicon quantum dots, epoxy, silicone, amino, polyoxyethylene and dicarboxymethylimino structures are introduced to prepare epoxy silicon quantum dot crosslinking agents with multiple functional groups on the surface for use with acrylamide Polymer-like cross-linking to form a high-strength, anti-aging frozen gel.

Benefits of technology

High-strength crosslinking is achieved at low concentrations, with good anti-aging ability and dispersion stability, which reduces product usage and improves the comprehensive performance of frozen gels. It is suitable for high-temperature and high-salt environments.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure FT_1
    Figure FT_1
  • Figure SMS_1
    Figure SMS_1
  • Figure SMS_2
    Figure SMS_2
Patent Text Reader

Abstract

The invention relates to a silicon quantum dot cross-linking agent for a gel type plugging agent and a preparation method of the silicon quantum dot cross-linking agent, and belongs to the technical field of oilfield chemistry. Silicon quantum dots are modified by a modifier containing epoxy and siloxane structures to prepare epoxy silicon quantum dots, and on the basis, the epoxy silicon quantum dots are modified by a modifier containing amino, polyoxyethylene and dicarboxymethyl imino structures to prepare the silicon quantum dots with various functional groups on the surfaces. The result test shows that under low concentration, the modified silicon quantum dots can well crosslink the acrylamide polymer, and the prepared gel is high in strength and has good anti-aging capability under high temperature and high salt. The gel cross-linking agent prepared by the invention has a wide application prospect in the aspect of profile control and water shutoff of high-temperature oil reservoirs.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to a silicon quantum dot cross-linking agent for a jelly-type plugging agent and a preparation method thereof, belonging to the technical field of oilfield chemistry. Background Art

[0002] Oil plays a vital role in the evolution of human civilization. It still occupies a dominant position in the world energy system and its consumption scale is still expanding. Therefore, in order to meet the growing demand for oil, the intensity of oil extraction will continue to increase. However, most of my country's oil fields have entered the middle and late stages of extraction, namely the tertiary oil recovery stage. The oil fields have high water content and serious water production. Exploiting the remaining oil and improving the recovery rate have become the main goals. Profile control and water plugging technology can increase the water drive swept volume by blocking the high permeability water flow channels in the reservoir, so that the crude oil in the porous medium can be displaced and the recovery rate can be improved. Therefore, it has received widespread attention as an important measure to increase production.

[0003] Profile control and water plugging are mainly divided into two categories: mechanical water plugging and chemical water plugging. Among them, gel plugging agents are widely used as a means of chemical plugging. Compared with mechanical methods, they have the advantages of low cost, simple construction process, and flexible plugging position. Gel plugging agents are mainly composed of polymers and cross-linking agents. At present, the cross-linking agents commonly used in oil fields are mainly divided into three categories: metal ion cross-linking agents, organic phenolic cross-linking agents, and polyethyleneimine cross-linking agents. Metal ion cross-linking agents react with carboxyl groups in polymers through coordination, but they have the disadvantages of too fast cross-linking speed and poor long-term stability of cross-linked gels; organic phenolic cross-linking agents react with amide groups in polymers through prepolymers, but they are easy to fail and are greatly affected by the environment; polyethyleneimine cross-linking agents react with amide groups in polymers through aminolysis, and their cross-linking time is controllable and the cross-linking strength is high, but they also have the disadvantages of high price, large dosage, and poor salt resistance. Silicon quantum dots are widely used as nanoparticles in the field of oilfield chemistry due to their unique physical structural properties. Their large specific surface area and particle characteristics provide more cross-linking sites and rigid structures. Therefore, developing a silicon quantum dot cross-linker carrying a large number of amino groups to replace polyethyleneimine cross-linkers is of great significance for reducing costs and improving the comprehensive performance of gels. Summary of the invention

[0004] In view of the deficiencies in the prior art, the present invention provides a silicon quantum dot cross-linking agent for a jelly-type plugging agent and a preparation method thereof. SUMMARY OF THE INVENTION

[0006] The present invention modifies silicon quantum dots by using a modifier containing epoxy and siloxane structures to prepare epoxy silicon quantum dots. On this basis, epoxy silicon quantum dots are modified by using a modifier containing amino, polyoxyethylene and dicarboxymethylimino structures to prepare silicon quantum dots with multiple functional groups on the surface. Test results show that at low concentrations, the modified silicon quantum dots can well cross-link acrylamide polymers, and the prepared jelly has high strength and good anti-aging ability under high temperature and high salt. DETAILED DESCRIPTION OF THE INVENTION

[0008] The technical solution of the present invention is as follows.

[0009] A silicon quantum dot crosslinking agent for a jelly-type plugging agent and a preparation method thereof, comprising the following steps:

[0010] (1) Preparation of epoxy silicon quantum dots

[0011] Mix deionized water and an organic solvent, add silicon quantum dots, perform ultrasonic dispersion, add modifier-1, adjust the pH to 5-12, react at 50-80°C for 3-8h, filter and dry the product to obtain a product; the particle size of the silicon quantum dots is 1-10nm, and the mass ratio of silicon quantum dots, modifier-1, deionized water and organic solvent is 1:(0.1-1):(1-3):(20-50);

[0012] (2) Preparation of silicon quantum dot crosslinker

[0013] Add epoxy silicon quantum dots into deionized water, disperse by ultrasonic, add modifier-2, modifier-3 and modifier-4 under stirring, the temperature is 30-70°C, react for 6-24h, filter and dry the product to obtain; the mass ratio of epoxy silicon quantum dots, modifier-2, modifier-3, modifier-4 and deionized water is 1:(0.1-3):(0.05-0.2):(0.1-1):(10-30).

[0014] According to the present invention, preferably, the average particle size of the silicon quantum dots in step (1) is 1 to 5 nm;

[0015] Preferably, the organic solvent is one of methanol, ethanol, n-propanol, isopropanol, acetone, dioxane, formamide, and N,N-dimethylformamide;

[0016] Preferably, the modifier-1 is one or a mixture of two or more of 3-glycidyloxypropyltrimethoxysilane, 3-glycidyloxypropyltriethoxysilane, 3-glycidyloxypropyldimethoxymethylsilane, 3-glycidyloxypropyldiethoxymethylsilane, 3-glycidyloxypropylmethoxydimethylsilane and 3-glycidyloxypropylethoxydimethylsilane;

[0017] Preferably, the mass ratio of silicon quantum dots, modifier-1, deionized water, and organic solvent is 1: (0.2-0.6): (1.5-2.5): (30-45);

[0018] Preferably, the pH is 6 to 8, the reaction temperature is 65 to 80° C., and the reaction time is 4 to 8 hours.

[0019] According to the present invention, preferably, the modifier modifier-2 described in step (2) is one or a mixture of two or more of ethylenediamine, propylenediamine, butylenediamine, pentanediamine, hexamethylenediamine, diethylenetriamine, triethylenetetramine, tetraethylenepentamine, pentaethylenehexamine, hexaethyleneheptamine, and heptaethyleneoctamine;

[0020] Preferably, modifier-3 is

[0021]

[0022] Where n is 5 to 40, R is -SO 3 Na, -CH 2 COONa, -H, -CH 3 、-CH 2 -CH 3 One of;

[0023] Preferably, modifier-4 is

[0024]

[0025] Where m is 1 to 6;

[0026] Preferably, the mass ratio of epoxy silicon quantum dots, modifier-2, modifier-3, modifier-4, and deionized water is 1:(0.5-2):(0.1-0.2):(0.2-0.8):(15-30);

[0027] Preferably, the reaction temperature is 40-65° C., and the reaction time is 8-18 h.

[0028] The excellent effects of the present invention are as follows:

[0029] 1. The raw materials of the present invention are easily available, the reaction conditions are mild, and the process is simple and safe.

[0030] 2. Taking advantage of the large surface area and size characteristics of silicon quantum dots, amino groups are loaded on the surface to provide sufficient cross-linking sites and suitable reaction structures, thereby reducing product dosage and improving cross-linking strength.

[0031] 3. By introducing ionic groups and polyethylene oxide segments on the surface of silicon quantum dots, the hydrophilicity of silicon quantum dots is improved to ensure that they still have good dispersion stability under high temperature and high salt conditions.

[0032] 4. Introduce dicarboxymethylimino structure on the surface of silicon quantum dots, and combine it with Ca 2+ Mg 2+ The interaction between ions reduces the impact of these ions on polymers and improves the anti-aging properties of the gel.

[0033] 5. Utilize the molecular rigidity of silicon quantum dots and their ability to form a composite structure with the polymer main chain to improve the temperature resistance and anti-aging properties of the gel.

[0034] 6. The product prepared by the present invention is easy to store and meets the requirements of environmental protection. BRIEF DESCRIPTION OF THE DRAWINGS Figure 1 This is a schematic diagram of the gel strength code. DETAILED DESCRIPTION

[0035] Unless otherwise specified, the experimental methods used in the following examples are conventional methods.

[0036] The silicon quantum dots used in the following examples were purchased from Jiangsu Xianfeng Nanomaterial Technology Co., Ltd., the acrylamide polymer was AN-105 produced by SNF, the polyethyleneimine crosslinker was CL-JY produced by Puyang Lutong Petrochemical Co., Ltd., and other raw materials were conventional commercial products.

[0037] The present invention is further described below in conjunction with specific embodiments, but the protection scope of the present invention is not limited thereto.

[0038] Embodiment 1:

[0039] (1) Preparation of epoxy silicon quantum dots

[0040] 10 g of deionized water and 200 g of dioxane were mixed, 6 g of silicon quantum dots with an average particle size of 2 to 3 nm were added, and ultrasonic dispersion was performed. 2.4 g of 3-glycidyloxypropyltrimethoxysilane was added, and the pH was adjusted to 7. The mixture was reacted at 80° C. for 4 h, filtered, and dried to obtain epoxy silicon quantum dot particles.

[0041] (2) Preparation of silicon quantum dot crosslinker

[0042] 5 g of epoxy silicon quantum dot particles were added into 100 g of deionized water, and ultrasonic dispersion was performed. 3 g of diethylenetriamine, 0.5 g of modifier-3, and 2.5 g of modifier-4 were added under stirring, and the mixture was reacted at 50° C. for 8 h. The product was filtered and dried to obtain a silicon quantum dot crosslinker.

[0043] Embodiment 2:

[0044] As described in Example 1, except that the organic solvent in step (1) is ethanol.

[0045] Embodiment 3:

[0046] As described in Example 1, except that the average particle size of the silicon quantum dots in step (1) is 4 to 5 nm.

[0047] Embodiment 4:

[0048] As described in Example 1, except that in step (1), the modifier-1 is 3-glycidyloxypropyldiethoxymethylsilane.

[0049] Embodiment 5:

[0050] As described in Example 1, except that in step (1), the amount of 3-glycidyloxypropyltrimethoxysilane added is 3.6 g.

[0051] Embodiment 6:

[0052] As described in Example 1, except that in step (1), the amount of silicon quantum dots added is 10 g.

[0053] Embodiment 7:

[0054] As described in Example 1, except that in step (1), the reaction temperature is 70° C. and the reaction time is 5 h.

[0055] Embodiment 8:

[0056] As described in Example 1, the difference is that in step (1), the organic solvent is 250 g of n-propanol and the modifier-1 is 3.6 g of 3-glycidyloxypropyldiethoxymethylsilane.

[0057] Embodiment 9:

[0058] As described in Example 1, except that in step (2), the reaction temperature is 60° C. and the reaction time is 10 h.

[0059] Embodiment 10:

[0060] As described in Example 1, the difference is that in step (2), the modifier-2 is ethylenediamine and triethylenetetramine.

[0061] Embodiment 11:

[0062] As described in Example 1, except that the amount of diethylenetriamine added in step (2) is 5 g.

[0063] Embodiment 12:

[0064] As described in Example 1, except that the amount of modifier-3 added in step (2) is 1 g.

[0065] Embodiment 13:

[0066] As described in Example 1, except that the amount of modifier-4 added in step (2) is 3 g.

[0067] Embodiment 14:

[0068] As described in Example 1, the difference is that in step (2), the amount of deionized water added is 75g, the amount of modifier-2 added is 2g of hexamethylenediamine and 2g of triethylenetetramine, and the amount of modifier-3 added is 1g.

[0069] Embodiment 15:

[0070] As described in Example 1, the difference is that in step (2), the amount of epoxy silicon quantum dot particles added is 4 g, the reaction time is 12 h, and the amount of modifier-4 added is 3 g.

[0071] Embodiment 16:

[0072] As described in Example 1, the difference is that in step (2), the modifier-2 is 5 g of pentaethylenehexamine, the amount of modifier-3 added is 0.7 g, and the amount of modifier-4 added is 4 g.

[0073] Performance Evaluation

[0074] Simulated formation water was prepared according to the composition in Table 1. Examples 1 to 16 were added to mineralized water at a concentration of 5000 mg / L and ultrasonically dispersed for 10 min, CL-JY was dissolved in mineralized water at a concentration of 12000 mg / L, and AN-105 was dissolved in mineralized water at a concentration of 20000 mg / L as mother liquor for standby use.

[0075] (1) Evaluation of gel strength

[0076] AN-105 and Example 1 or CL-JY were mixed at target concentrations, added to a glass pressure tube and sealed. The glass pressure tube was placed in a constant temperature oven at 130°C, and the gelling dynamics were determined by observing the gel flow state and the gel state changing with time. The gel system can be divided into 9 grades (A to I) according to the different flow states, suspension states and tongue-out states of the gel, such as Figure 1 The gel strength is defined as the strength level when the gel strength in the glass pressure tube no longer changes. The results are shown in Table 2.

[0077] (2) Evaluation of salt resistance and long-term stability

[0078] AN-105 and Example 1 or CL-JY were mixed at a volume ratio of 1:1 and added into a glass pressure tube and then sealed. The glass pressure tube was placed in a constant temperature oven at 130°C, and the dehydration amount of the gel after aging for 30 days, 90 days, and 120 days was recorded. The dehydration rate of the gel was calculated according to the following formula. The results are shown in Table 3.

[0079]

[0080] Wherein, WR-dehydration rate, %;

[0081] V 0 - Volume of the jelly when gelled, mL;

[0082] V t - Volume of the gel after aging time t, mL.

[0083] Table 1 Composition of simulated formation water

[0084]

[0085] Table 2 Gel strength of samples with different concentrations

[0086] Sample No. <![CDATA[Crosslinking agent concentration / mg·L -1 > <![CDATA[Polymer concentration / mg·L -1 > Gel strength CL-JY 5000 8000 E CL-JY 6000 8000 F CL-JY 6000 10000 G Example 1 1000 8000 H Example 1 2000 8000 I Example 1 2000 10000 I

[0087] Table 3 Gel strength, salt resistance and long-term stability of different samples

[0088] Sample No. Gel strength 30-day dehydration rate (%) 90-day dehydration rate (%) 120-day dehydration rate (%) CL-JY G 8.9 25.7 38.9 Example 1 H 2.2 7.9 13.4 Example 2 H 2.0 7.3 12.5 Example 3 H 2.4 8.1 14.1 Example 4 H 1.9 7.5 11.3 Example 5 I 1.1 6.8 9.4 Example 6 I 1.3 7.2 9.5 Example 7 H 1.5 7.4 10.5 Example 8 I 1.4 7.7 10.1 Example 9 I 0.9 6.7 8.6 Example 10 H 1.6 7.5 11.1 Embodiment 11 I 1.8 7.8 11.9 Example 12 I 1.7 7.3 11.3 Example 13 H 2.2 7.8 13.1 Embodiment 14 I 1.5 7.3 10.9 Embodiment 15 I 0.9 6.7 8.6 Example 16 I 1.1 6.9 9.0

[0089] As can be seen from Table 2, compared with conventional polyethyleneimine crosslinking agents, the crosslinking agent prepared in the present invention has a small dosage and high gel strength after crosslinking with acrylamide polymers at low concentrations; as can be seen from Table 3, the gel strength of all gel systems prepared by the crosslinking agent of the present invention can reach above Grade H. After gelation, the gel has excellent anti-aging properties, and after 120 days of aging, the dehydration rate is about 10%.

Claims

1. A silicon quantum dot crosslinking agent for a jelly-type plugging agent and a preparation method thereof, comprising the following steps: (1) Preparation of epoxy silicon quantum dots Mix deionized water and an organic solvent, add silicon quantum dots, perform ultrasonic dispersion, add modifier-1, adjust the pH to 5-12, react at 50-80°C for 3-8h, filter and dry the product to obtain a product; the particle size of the silicon quantum dots is 1-10nm, and the mass ratio of silicon quantum dots, modifier-1, deionized water and organic solvent is 1:(0.1-1):(1-3):(20-50); The organic solvent is one of methanol, ethanol, n-propanol, isopropanol, acetone, dioxane, formamide, and N,N-dimethylformamide; Modifier-1 is one or a mixture of two or more of 3-glycidyloxypropyltrimethoxysilane, 3-glycidyloxypropyltriethoxysilane, 3-glycidyloxypropyldimethoxymethylsilane, 3-glycidyloxypropyldiethoxymethylsilane, 3-glycidyloxypropylmethoxydimethylsilane and 3-glycidyloxypropylethoxydimethylsilane; (2) Preparation of cross-linking agent Add epoxy silicon quantum dots to deionized water, disperse by ultrasonic, add modifier-2, modifier-3, and modifier-4 under stirring, the temperature is 30-70°C, react for 6-24h, filter and dry the product to obtain; the mass ratio of epoxy silicon quantum dots, modifier-2, modifier-3, modifier-4, and deionized water is 1:(0.1-3):(0.05-0.2):(0.1-1):(10-30); Modifier-2 is one or a mixture of two or more of ethylenediamine, propylenediamine, butylenediamine, pentanediamine, hexamethylenediamine, diethylenetriamine, triethylenetetramine, tetraethylenepentamine, pentaethylenehexamine, hexaethyleneheptamine, and heptaethyleneoctamine; Modifier-3 is wherein n is 5 to 40, and R is one of -SO3Na, -CH2COONa, -H, -CH3, and -CH2-CH3; Modifier-4 is Where m is 1 to 6.

2. The silicon quantum dot crosslinking agent for jelly-type plugging agent and the preparation method thereof according to claim 1, characterized in that: The particle size of the silicon quantum dots in step (1) is 1 to 5 nm.

3. The silicon quantum dot crosslinking agent for jelly-type plugging agent and the preparation method thereof according to claim 1, characterized in that: In step (1), the mass ratio of silicon quantum dots, modifier-1, deionized water and organic solvent is 1: (0.2-0.6): (1.5-2.5): (30-45).

4. The silicon quantum dot crosslinking agent for jelly-type plugging agent and the preparation method thereof according to claim 1, characterized in that: In step (1), the reaction pH is 6 to 8, the reaction temperature is 65 to 80° C., and the reaction time is 4 to 8 hours.

5. The silicon quantum dot crosslinking agent for jelly-type plugging agent and the preparation method thereof according to claim 1, characterized in that: In step (2), the mass ratio of epoxy silicon quantum dots, modifier-2, modifier-3, modifier-4, and deionized water is 1:(0.5-2):(0.1-0.2):(0.2-0.8):(15-30).

6. The silicon quantum dot crosslinking agent for jelly-type plugging agent and the preparation method thereof according to claim 1, characterized in that: In step (2), the reaction temperature is 40-65° C. and the reaction time is 8-18 h.

Citation Information

Patent Citations

  • Slow cross-linking gel for profile control of medium-high temperature oil reservoir and preparation method of slow cross-linking gel

    CN113249102A

  • Preparation method of cross-linking agent for acrylamide polymer type gel

    CN117756980A

  • Delayed cross-linking silicon dot nano cross-linking agent as well as preparation method and application thereof

    CN118206975A

  • Insoluble chemical composite material

    EP0239079A2